Interview feedback from Six Educationists and Six Economists on electronic levy legislation in Ghana - Moses Kumi Asamoah; Edward Nketiah-Amponsah; Joseph Danquah Ansong (Cogent Social Sciences, 2023)
AbstractThis study aimed at addressing the controversies regarding the legislation of an e-levy in Ghana to ensure that its implementation is successful. Qualitative exploratory design and interviews were used for the study. Twelve lecturers (PhD holders) were judgmentally sampled for the study. Research ethics and data credibility procedures were followed. A section of the research participants was in favour of the e-levy legislation as a key avenue to generate additional revenue, and those opposed to the legislation maintain that the e-levy is regressive, punitive, and depressive. It was concluded that a section of Ghanaians supports the e-levy on account of its revenue yield potential with far reaching implications for developmental projects. However, serious concerns about the e-levy have been raised regarding its design, particularly the rate and exemptions, the timing of its implementations, accountability, and corruption of public officials. Recommendations are as follows: e-levy should be pegged at 0.5% per electronic transaction above Ghc100; the waste in the system, extravagant spending from state revenue as well as corruption by government officials should be addressed sternly; and there should be adequate public education on the e-levy concept. This is one of the foremost qualitative studies conducted on e-levy in Ghana, contributing to e-levy legislation and management literature. The paper is a novel because it has an E-levy Conversation Model as well as an E-levy Acceptance Model, developed from the empirical data to guide the successful legislation and acceptance of e-levy in Ghana, and Africa as a whole.